Visitors' satisfaction with facilities at Ulu Bendul Forest Eco Park - Abdul Aziz, Nor Akmar; Omran, Muhammad Haziq; Mohamed Mokhtar, Mohamed Daniel; Raman, Thivya Laxshmy; Md Yusop, Mohd Yussainy; Saikim, Fiffy Hanisdah; Mohd Nordin, Nordiana (Malaysian Forester, 2022)
Ulu Bendul Forest Eco Park is a popular destination among tourists whether domestic or international. It is situated in the state of Negeri Sembilan and is relatively near to Kuala Lumpur, the capital of Malaysia. In recent years, online reviews and comments by visitors to the park have been somewhat negative, however, there is no empirical study as of yet that investigates the satisfaction levels among visitors. Hence, this study was conducted to assess the satisfaction level among visitors of Ulu Bendul Forest Eco Park towards the existing facilities provided in the park. This study used an adapted version of the Customer Satisfaction Index to identify satisfaction levels among visitors dubbed the Visitor Satisfaction Index (VSI). The method for data collection is convenience sampling. A total of 150 respondents were surveyed between March and June 2020. After analysis, respondents were categorized into three groups based on their satisfaction index: low, intermediate and high satisfaction levels. Results indicate that the group with intermediate satisfaction level is highest in frequency among visitors, and this suggests that there are opportunities for improvement in terms of facilities in Ulu Bendul Forest Eco Park. Results also showed that the swimming pool and signage need improvement.